2018
DOI: 10.1016/j.jclepro.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The influence of motivations and barriers in the benefits. An empirical study of EMAS certified business in Spain

Abstract: The main objective of this research is to analyze through a structured questionnaire, the influence of the motivations that lead companies to implement Eco-Management and Audit Scheme (EMAS) and the barriers found in the benefits perceived by companies, as well as, the degree of difficulty perceived for the implementation of the different requirements to be fulfilled, which are established in the regulation. An extensive review of the academic literature published on motivations, barriers, difficulties and ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…Motivations and outcomes of standard-based EMS adoption have attracted considerable interest in management research (Stevens et al, 2012;Boiral et al, 2018;Salim et al, 2018;Álvarez-García et al, 2018). Studies have demonstrated that certified EMS adoption contributes enhancing corporate legitimacy and reputation in the eyes of external stakeholders, by signalling superior environmental commitment, reliability and transparency (Bansal and Hunter, 2003;King and Bruner, 2000;Darnall, 2006;Tambovceva and Geipele, 2011;D'Souza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Motivations and outcomes of standard-based EMS adoption have attracted considerable interest in management research (Stevens et al, 2012;Boiral et al, 2018;Salim et al, 2018;Álvarez-García et al, 2018). Studies have demonstrated that certified EMS adoption contributes enhancing corporate legitimacy and reputation in the eyes of external stakeholders, by signalling superior environmental commitment, reliability and transparency (Bansal and Hunter, 2003;King and Bruner, 2000;Darnall, 2006;Tambovceva and Geipele, 2011;D'Souza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to find the optimum mixture of oxygenates, it is essential to evaluate the balance between engine performance and eco-indicators, where the preferred priority of the indicators allows to ensure the compatibility of all engine parameters depending on the load and the advance angle of the engine, allowing to change the time of fuel injection, and directly affecting the combustion process. An expert survey was carried out to assess the importance of engine performance and environmental performance, during which experts put a priority ranking of indicators [75].…”
Section: Results Of Experimental Investigation Of the Internal Combusmentioning
confidence: 99%
“…Económica Agraria. of standards adopted at a strategic and operational level that allow companies to properly comply with environmental standards by contributing in this way, specifically for the improvement of the environment [18]. In addition, both certifications are voluntary and environmental management allows for more positive economic [19] and environmental [17,[20][21][22] effects.…”
Section: Ite-información Técnicamentioning
confidence: 99%
“…As far as EMSs are concerned, there are two widely accepted systems worldwide, the international standard ISO 14001 (created by the International Organization for Standardization-ISO) and the European Union regulation Eco-Management and Audit Scheme (EMAS). Both EMAS and ISO 14001 are voluntary systems that provide impartial third-party assurance of the correct management of standards adopted at a strategic and operational level that allow companies to properly comply with environmental standards by contributing in this way, specifically for the improvement of the environment [18]. In addition, both certifications are voluntary and environmental management allows for more positive economic [19] and environmental [17,[20][21][22] effects.…”
Section: Introductionmentioning
confidence: 99%